Association of Serum Biomarkers With Post-Thrombolytic Symptomatic Intracranial Hemorrhage in Stroke: A Comprehensive Protein Microarray Analysis From INTRECIS Study - Cui, Yu; Zhao, Yong; Chen, Shao-Yuan; Sheng, Bao-Ying; Wang, Li-Hua; Meng, Wei-Hong; Chen, Hui-Sheng (Frontiers in Neurology, 2022)
Background Symptomatic intracranial hemorrhage (sICH) after intravenous thrombolysis is closely related to the poor outcome of stroke. Aims To determine the serum biomarkers associated with sICH based on the INTRECIS study. Methods Enrolled patients with sICH and without any ICH were matched by propensity score matching with the ratio of 1:1. Preset 49 biomarkers were measured by protein microarray analysis. Gene Ontology and Pathway Enrichment Analysis and protein-protein interaction network (PPI) were analyzed in the identified biomarkers. Results Of the consecutive 358 patients, eight patients occurred with sICH, which was assigned as an sICH group, while eight matched patients without any ICH were assigned as a Non-sICH group. A total of nine biomarkers were found significantly different between groups, among which the levels of interferon (IFN)-γ and interleukin (IL)-4 were higher, while the levels of C-reactive protein (CRP), glial cell line-derived neurotrophic factor (GDNF), insulin-like growth factor-binding protein (IGFBP)-6, lymphatic vessel endothelial hyaluronan receptor (LYVE)-1, matrix metalloprotein (MMP)-2, plasminogen activator inhibitor (PAI)-1, and platelet-derived growth factor (PDGF)-AA were lower in the sICH group compared with those in the Non-sICH group. Conclusions Our finding indicated that baseline serum CRP, GDNF, IFN-γ, IGFBP-6, IL-4, LYVE-1, MMP-2, PAI-1, and PDGF-AA levels were associated with post-thrombolytic sICH in stroke.